Investigating Student’s Learning Difficulties in Shape and Space Topic: A Case Study (International Journal of Psychosocial Rehabilitation, 2020)
Learning difficulties in mathematics cause students to struggle with the numbers, formulas, calculations, concepts, and related shapes because it takes students’ patience and persistence. Therefore, the objective of this study is to investigate the learning difficulties encountered by students in the ‘Shape and Space’ topic. The contributing factors for such difficulties are also studied. Forty Standard Two (2) students from a primary school in Kuala Selangor participated in this case study. The purposive sampling technique is used in this study. It was found that there are a few difficulties and their contributing factors encountered by the respondents. A test and semi structured interview were the instruments used for the data collection. The research findings show that 70% of the respondents are having difficulty in understanding and answering the questions related to the subtopics involving types of straight and curved surfaces and the number of shape surfaces. Additionally, 80% of the respondents are having difficulty in the subtopic of 3-dimensional stretch of shape and how to draw them. The difficulties faced by the students are because of the inability to imagine the shape and the stretch (imagination) and the inability to understand the stretch of the combined basic shape. Therefore, this study proposes the steps and initiatives for teachers in planning suitable learning activities to help the students in overcoming their difficulties.